What are the Challenges and Motivations of Combining Nursing and Motherhood? - Brickell-Bowers, Lyndsey (2014)
Abstract To examine the challenges and motivations of combining nursing and motherhood in Britain, a qualitative, social constructivist approach has been undertaken and NHS nurses have been interviewed. Social constructionist feminism inspires this article and according to this analysis, three main themes were discovered. Women’s combination of nursing and motherhood creates a unique position of constantly caring. A serious side-effect of women’s position as carers, who put others needs before their own, is its cost to their own health and well-being. Women describe enabling factors that facilitate their combination of nursing and motherhood such as familial support networks that assist with child care and child care costs and personal time out for themselves. Some women are constructing their motherhood aside from dominant concepts of womanhood and motherhood and view employment as positive, justified on the basis of personal gains and benefits for the children. British-born women with access to maximum enabling factors have a positive experience of nursing alongside motherhood whereas none-British nurses, without certain crucial enabling factors have a negative experience of nursing alongside motherhood. Themes are discussed in relation to the underlying concept of women’s inequality.